Pengaruh Modifikasi Lingkungan terhadap Status Fisiologis Sapi Perah di Lahan Kering - Theresia Ika Purwantiningsih; Remigius Binsasi; Orlando Chaves Araujo (Universitas Sebelas Maret, 2022)
Objective: This study was conducted to determine the physiological status of dairy cows reared in dry land, for example in East Nusa Tenggara (NTT) treated with shade-tethering and housed in a housing with fan.Methods: This research was conducted for 60 days. Three lactation dairy cows Friesien Holstein (FH) cows used in this research. The method used in this study is an experimental method by observing the environmental temperature and physiological status directly on 3 lactating dairy cows that are tethered in the shade and housed in a house that is equipped with a fan. Data were analyzed using Paired T – Test analysis.Results: The results showed that the temperature in the house with the fan was lower (25.80ᵒC) than in the shade (27.90ᵒC). The respiration and pulse of cows housed with fans were lower than cows reared in shade. The rectal temperature of cows housed with fans was not much different from that of cows kept in shade.Conclusions: The ambient temperature in the fan-cooled enclosure is lower than the ambient temperature in the shade. So that it affects the lower respiration frequency and pulse in cows housed with fans.